Polycomb repressor complex 2 function in breast cancer (Review) - Martin, Courtney J. (Int J Oncol, 2020)
Epigenetic modifications are important contributors to the regulation of genes within the chromatin. The poly-comb repressive complex 2 (PRC2) is a multi-subunit protein complex that is involved in silencing gene expression through the trimethylation of lysine 27 at histone 3 (H3K27me3). The dysregulation of this modification has been associated with tumorigenicity through the increased repression of tumour suppressor genes via condensing DNA to reduce access to the transcription start site (TSS) within tumor suppressor gene promoters. In the present review, the core proteins of PRC2, as well as key accessory proteins, will be described. In addition, mechanisms controlling the recruitment of the PRC2 complex to H3K27 will be outlined. Finally, literature identifying the role of PRC2 in breast cancer proliferation, apoptosis and migration, including the potential roles of long non-coding RNAs and the miR-200 family will be summarized as will the potential use of the PRC2 complex as a therapeutic target.